2022
DOI: 10.1111/jftr.12456
|View full text |Cite
|
Sign up to set email alerts
|

The procreative identities of men in same‐sex relationships choosing surrogacy: A new theoretical understanding

Abstract: The growing visibility of same‐sex two‐parent families and the increased use of surrogacy have expanded LGBT parenting scholarship to include experiences of gay and other men in same‐sex relationships. Yet, even with the growth of research over the past decade on gay and other sexual minority men's parenting experiences, such studies are still undertheorized. The purpose of this article is to conceptualize an enhanced family theory model that addresses the evolution of the procreative identities of men in same… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 140 publications
0
6
0
Order By: Relevance
“…This study enriches the procreative identity framework (Berkowitz & Marsiglio, 2007 ), originally proposed to describe how cisgender heterosexual men make reproductive decisions and react to pregnancy loss, miscarriage, and abortion. Fantus and Newman ( 2022 ) have revisited this framework by accounting for sexual minority men’s distinctive experiences, suggesting that gay men’s procreative consciousness is widely tied to individual life events, romantic interpersonal relationships, and sociohistorical contexts. Building on this framework, the current study with Taiwanese gay men in same-sex relationships delineates the role of sociocultural factors in fostering men’s desire for parenthood, identifying that gay men’s procreative consciousness partly depends on their attitudes towards marriage.…”
Section: Discussionmentioning
confidence: 99%
“…This study enriches the procreative identity framework (Berkowitz & Marsiglio, 2007 ), originally proposed to describe how cisgender heterosexual men make reproductive decisions and react to pregnancy loss, miscarriage, and abortion. Fantus and Newman ( 2022 ) have revisited this framework by accounting for sexual minority men’s distinctive experiences, suggesting that gay men’s procreative consciousness is widely tied to individual life events, romantic interpersonal relationships, and sociohistorical contexts. Building on this framework, the current study with Taiwanese gay men in same-sex relationships delineates the role of sociocultural factors in fostering men’s desire for parenthood, identifying that gay men’s procreative consciousness partly depends on their attitudes towards marriage.…”
Section: Discussionmentioning
confidence: 99%
“…Certainly, there is some evidence that heteronormativity (i.e., a hierarchy in society that privileges heterosexual ways of behaviour and frequently a central assumption of hegemonic masculinity) and attendant stigma are key sources of distress for gay fathers [42,43], particularly for those at the intersection of constructions of race and single fatherhood [44]. Moreover, gay fathers' encounters of homophobia-in the form of daily microaggressions, the complexities of disclosure of surrogacy, and repeatedly having to "come out" due to heteronormative biases-may also contribute to experiences of distress [10]. Thus, more needs to be done to understand the ways in which gay fathers' experiences of surrogacy and early parenthood both require a negotiation with others when it comes to masculinity, as well as the potentials to challenge hegemony [44,45].…”
Section: Psychological Distress In Gay Fathersmentioning
confidence: 99%
“…For instance, research has shown how some men struggle to negotiate the identity "gay father", particularly when faced with heterosexist norms and feelings of internalised shame [47]. Third, the route to gay fatherhood via surrogacy presents unique logistical, legal, and emotional challenges [10,39]. For instance, surrogacy often involves lengthy wait times, high levels of uncertainty, and cycles of hope and disappointment if arrangements fail [48].…”
Section: Psychological Distress In Gay Fathersmentioning
confidence: 99%
See 2 more Smart Citations